Influence of the partical size of emulsion on the stability of bevereges - Sidor, Vasyl; Lugovska, Oksana (My University, 2017)
Beverage emulsions containing particles with a size of 1-1000 nm, and treated as objects of classical colloid chemistry. Of great importance to the stability of food products has a particle size. The use of emulsions in the manufacture of beverages is associated with the possibility of reducing the length of the production process while reducing power consumption compared to traditional production methods. This difference is particularly useful in food industry, because of the emulsions are the necessary ingredients that provide flavor, color and aroma of food that greatly simplifies their production technology.
Keywords: кафедра експертизи харчових продуктів; stabilizer; particle size; emulsion; phase; stability; стабілізатор; емульсії; розмір частинок; фази; стабільність; стабилизатор; размер частиц; эмульсии; фазы; стабильность